Efeito do plasma atmosférico não-térmico, do condicionamento ácido e do envelhecimento na resistência de união de um adesivo universal ao esmalte dental humano - Ribas, Mariana Macedo (2020)
This study in vitro evaluated the effect of non-thermal atmospheric plasma on the bond strength (BS) of a universal adhesive to human enamel, with or without acid etching, when subjected to aging. Twenty molars were sectioned in the buccolingual direction to obtain 40 proximal enamel surfaces. These were planned, polished and randomly assigned to 4 groups (n = 10) according to acid etching ([Et], [no-Et]) and plasma treatment ([P], [no-P]): Et/P, Et/no-P, noEt/P, no-Et/no-P. 37% phosphoric acid gel was used for conditioning and plasma was applied on the enamel surface for 20 seconds by scanning mode. Afterwards, Scothbond Universal Adhesive [SBU] was actively applied and a composite resin block was incrementally built up (Filtek Z100, 3M ESPE). After 24 hours of storage in deionized water, the specimens were sectioned into sticks (area 1.0 ± 0.2 mm; 10 per group). Then, half of the sticks in each group were immediately submitted to the µTBS test (0.5 mm / s) [24h] and the remaining half after 12 months of aging [12m]. Data were submitted to three-way ANOVA with subdivided plots (p <0.01) followed by Tukey test (<0.05). Fractured surfaces were analyzed by digital optical microscopy (100% magnification) to determine the failure mode. The three isolated factors showed statistical difference: time (p <0.001), plasma (p = 0.04) and acid etching (p = 0.006). There was significant interaction only for time-acid etching (p = 0.013). The acid conditioning of enamel increased the BS values after immediate traction, effect not observed for plasma. The highest BS value was observed for the Et/no-P/24h group. Aging after 12 months significantly reduced the BS of all groups without statistical difference between them. The authors concluded that, unlike phosphoric acid etching, plasma application did not increase enamel BS. Aging of the samples had a negative effect on the BS values.